Development of dietary fiber enriched chicken sausage using wheat bran - Shanaullah, M; Habib, M; Hashem, MA; Azad, MAK; Ali, MS (Meat Research, 2024)
The study was conducted to evaluate the effect of wheat bran on the sensory, physicochemical, and biochemical properties of chicken sausages. For this purpose, sausages were prepared into 4 different groups. Such as: control- broiler breast meat sausage without wheat bran, broiler breast meat sausage with the addition of 5% wheat bran, broiler breast meat sausage with the addition of 10% wheat bran, broiler breast meat sausage with the addition of 15% wheat bran. All parameters were analyzed at 0, 14 and 28 days of storage period. The surface color (CIE L*, a*, b*) of sausage samples were measured using a colorimetric meter at different storage period. The proximate composition, pH and cooking loss of different sausage batter were analyzed and significant differences were found in DM%, CF%, CP%, Ash%, EE%, and pH. The DM and CF% were significantly lower, while CP% was higher in control sausage batter. Highly significant (p<0.01) differences were found in DM, CP, CF, and Ash % in broiler breast meat sausages. DM, CF, and Ash% were significantly lower and CP% was higher in control sausage. Both CP and CF content were increased, but Ash and Fat content decreased with the increase of storage time. The storage period has significant effect (p<0.01) on different biochemical (POV and TBARS value) tests. POV and TBARS were increased with increasing the storage period. Lightness (L*) value showed significant (p<0.05) differences among different treatments and different storage period. Significantly (p<0.05) lower lightness and yellowness were found in broiler breast meat sausage without wheat bran. Again, redness and yellowness were decreased with increasing the storage period. In sensory analysis, flavor and overall acceptability were significantly higher in broiler breast meat sausages with 5% wheat bran (p<0.05). Taken together it may conclude that wheat bran at 5% level might be incorporated in broiler breast meat sausages with higher overall acceptability.